Perspectives on Sexual Health and Function of Recent Male Combat Veterans of Iraq and Afghanistan. Issue 3 (8th May 2015) - Helmer, Drew A.; Beaulieu, Gregory; Powers, Catherine; Houlette, Cheryl; Latini, David; Kauth, Michael
Abstract: Background: U.S. veterans of recent wars in Iraq and Afghanistan may be at greater risk for sexual dysfunction due to injuries, mental health conditions, medications used to treat those conditions, and psychosocial factors. Objective: To explore the perceptions of recent Veterans about sexual health and dysfunction, contributing factors, its impact and solutions. Design: Qualitative study. Participants: Eight men who screened positive for sexual dysfunction at initial presentation to a postdeployment clinic at a Veterans Affairs medical center Approach: Patients who screened positive for sexual dysfunction and indicated an interest in participating were contacted and scheduled for an in‐person private interview with a researcher. Interviews were semistructured, utilizing open‐ended and follow‐up probe questions to elicit the individual's perspective about sexual dysfunction and its cause, impact and solutions. Interviews were recorded, transcribed and analyzed for themes. Key Results: These heterosexual men discussed a range of sexual dysfunction in their activities including lack of desire, erectile dysfunction, delayed orgasm, premature ejaculation, and distraction. They also discussed the importance of setting or context and changes over time to their sexual health and function. The men shared their ideas about contributory factors, including normal aging, medication side effects, injury and a possible role for combat deployment more generally. Reported solutions for sexual dysfunction included medications, herbal remedies, and new positions and approaches to sexual activity. Participants reported discussing sexual dysfunction with their health‐care providers and what was helpful. Finally, the men expressed in their own words the significant impact of sexual dysfunction on their self‐perception, their partners, and their relationships. Conclusions: Sexual dysfunction in recent combat veterans can have important negative effects on their health and relationships. Our findings elucidate perceived contributory factors and preferred solutions, which can be applied by health‐care providers to improve the management of sexual dysfunction in these patients.Helmer DA, Beaulieu G, Powers C, Houlette C, Latini D, and Kauth M. Perspectives on sexual health and function of recent male combat veterans of Iraq and Afghanistan. Sex Med 2015;3:137–146.